2003
DOI: 10.1099/mic.0.26228-0
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of the uracil-DNA glycosylase inhibitor protein, Ugi, with Mycobacterium smegmatis and Mycobacterium tuberculosis uracil-DNA glycosylases

Abstract: Uracil, a promutagenic base, appears in DNA either by deamination of cytosine or by incorporation of dUMP by DNA polymerases. This unconventional base in DNA is removed by uracil-DNA glycosylase (UDG). Interestingly, a bacteriophage-encoded short polypeptide, UDG inhibitor (Ugi), specifically inhibits UDGs by forming a tight complex. Three-dimensional structures of the complexes of Ugi with UDGs from Escherichia coli, human and herpes simplex virus have shown that two of the structural elements in Ugi, the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…As shown in Fig. 2(a), the purified protein (MSMEG_5031) excises uracil from GU9, a dsDNA substrate (S) containing uracil in a G : U pair at position 9 from the 59 end, and generates a product (P); and this activity is insensitive to the presence of Ugi, a highly specific Bacillus subtilis phage PBS1-encoded proteinaceous inhibitor (Acharya et al, 2003) of the family 1 UDGs (lanes 3-5). The MSMEG_5031-encoded protein did not show uracil excision activity on SSU9, an ssDNA substrate containing uracil within the same sequence context as dsDNA (lanes 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 2(a), the purified protein (MSMEG_5031) excises uracil from GU9, a dsDNA substrate (S) containing uracil in a G : U pair at position 9 from the 59 end, and generates a product (P); and this activity is insensitive to the presence of Ugi, a highly specific Bacillus subtilis phage PBS1-encoded proteinaceous inhibitor (Acharya et al, 2003) of the family 1 UDGs (lanes 3-5). The MSMEG_5031-encoded protein did not show uracil excision activity on SSU9, an ssDNA substrate containing uracil within the same sequence context as dsDNA (lanes 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…This protein, uracil-DNA glycosylase inhibitor (Ugi), abolishes Ung activity in both bacteria and humans (Acharya et al, 2003;Olsen et al, 1991;Wang & Mosbaugh, 1988), and has been shown to increase mutation frequency when expressed in human cells (Radany et al, 2000). In addition to Ugi, PBS2 expresses a set of enzymes that function cooperatively to increase the intracellular dUTP pool and decrease the TTP concentration, thus resulting in the close to 100 % incorporation of dU instead of T in the DNA (Wang & Mosbaugh, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…If this hypothesis is correct, inhibition of virion-associated UNG2 could lead to less abasic site(s) in newly synthesized viral DNA chains and less degradation of newly synthesized viral DNA, and subsequently, less viral infectivity. Therefore we employed Ugi, a bacteriophage-encoded short polypeptide that can tightly bind to the DNA-binding site of UNG2, to inhibit the catalyzing activity of UNG2 in either virus-producing cells or viral target cells (23)(24)(25)(26)(27)(28). We have transfected Ugi-expressing vector in virus-producing 293T cells or viral target cells (HLCD4-CAT), respectively.…”
Section: Expression Of Ung2-inhbitor Ugi or Ung2-specific Sirna Inmentioning
confidence: 99%